Patient-specific therapeutic benefit of MuSK agonist antibody ARGX-119 in MuSK myasthenia gravis passive transfer models - Jamie L. Lim; Stine Marie Jensen; Jaap J. Plomp; Bernhardt Vankerckhoven; Christa Kneip; Rani Coppejans; Christophe Steyaert; Kathleen Moens; Lieselot De Clercq; Martijn R. Tannemaat; Peter Ulrichts; Karen Silence; et al. (iScience)
Summary: Muscle-specific kinase (MuSK) orchestrates the establishment and maintenance of neuromuscular synapses. Autoantibodies targeting MuSK cause myasthenia gravis (MG), a disease characterized by skeletal muscle weakness. MuSK autoantibodies are predominantly IgG4 which are bispecific, functionally monovalent antibodies that are antagonists of MuSK signaling. We hypothesized that bivalent MuSK agonist antibodies can rescue MuSK MG. Here, we investigated whether ARGX-119, a MuSK frizzled-like domain agonist antibody, can ameliorate disease in passive transfer models induced by polyclonal patient IgG4. ARGX-119 improved survival and muscle weakness in a mouse model induced by one patient material, but not by three others. Patient-specific efficacy could not be explained by titer or competition for ARGX-119 binding, but rather correlated with the presence of MuSK activating antibodies in some patients. This first proof of concept of a MuSK agonist in a clinically relevant MuSK MG model forms a starting point for therapeutic studies toward ARGX-119 efficacy in neuromuscular diseases.